Does professional knowledge management improve innovation performance at the firm level? - Dirk Czarnitzki; Annelies Wastyn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The concept of knowledge has gained in interest since industrialized economics have induced a shift in importance from labor, capital and natural resources towards intellectual resources. This study investigates how the management of knowledge influences the innovation performance of a firm. While former studies mainly focused on knowledge management cycles, we distinguish different types of knowledge management techniques. It turns out that there is a difference between three knowledge management techniques and their influence on product and process innovation. The ability to source external knowledge positively affects the firm's introduction of new products and products new to the market. For obtaining cost reductions it is effective to stimulate employees to share knowledge. The availability of a codified knowledge management policy also positively affects the cost reduction possibilities of a firm. These results indicate that it is important for a firm to carefully select the tools of knowledge management in function of the kind of technical innovation it wants to proceed.
Keywords: O31; O32; 330; Knowledge management; innovation performance; Wissensmanagement; Innovation; Unternehmensentwicklung; Deutschland